Cracks and Other Short Stories - Munyoro, Albert (Book collections on Project MUSE., 2020)
There are little strokes that fell great oaks and often unattended cracks in a diversity of our socio-economic and political institutions can ultimately lead to a total collapse of systems. Cracks and Other Short Stories is an anthology that offers readers an insight into some of the major cracks in our personalities and institutions as a subtle means of encouraging everyone to investigate them further and seek lasting solutions for the good of humanity. Cracks signal that things are out of sorts and need timeous repair, healing and mending before systems become dysfunctional and torturous to humanity. Thus, each story in this impeccable collection deals with specific metaphorical cracks which require problem solving for the betterment of society.